Complete genome sequence of Acidimicrobium ferrooxidans type strain (ICPT). Issue 1 (July 2009) - Clum, Alicia; Nolan, Matt; Lang, Elke; Rio, Tijana; Tice, Hope; Copeland, Alex; Cheng, Jan-Fang; Lucas, Susan; Chen, Feng; Bruce, David; Goodwin, Lynne; Pitluck, Sam; et al.
Abstract Acidimicrobium ferrooxidans (Clark and Norris 1996) is the sole and type species of the genus, which until recently was the only genus within the actinobacterial familyAcidimicrobiaceae and in the orderAcidomicrobiales . Rapid oxidation of iron pyrite during autotrophic growth in the absence of an enhanced CO2 concentration is characteristic forA. ferrooxidans . Here we describe the features of this organism, together with the complete genome sequence, and annotation. This is the first complete genome sequence of the orderAcidomicrobiales, and the 2, 158, 157 bp long single replicon genome with its 2038 protein coding and 54 RNA genes is part of theG enomic E ncyclopedia of B acteria and A rchaea project.